Glue for copper-clad laminate and preparation method of copper-clad laminate

Through the preparation of modified epoxy resins and fillers, the problem of heat resistance, thermal conductivity and mechanical properties of the existing copper covering plates is solved. Interconnection and integrated circuits.

CN115678205BActive Publication Date: 2025-01-28ANHUI HON HAI NEW MATERIALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211286173.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-20
Publication Date
2025-01-28
Estimated Expiration
2042-10-20

AI Technical Summary

Technical Problem

The existing copper clad plates have insufficient heat resistance, thermal conductivity and mechanical properties, making it difficult to meet the needs of high-density interconnection and integrated circuits. At the same time, the use of a large number of inorganic fillers leads to processing difficulties and performance degradation.

Method used

Through the preparation of modified epoxy resin and modified fillers, the introduction of silicon group and seventeen fluorinity triaxyxyxilanes to improve the thermal stability and thermal conductivity of the rubber liquid; Sexuality and compatibility, forming armal network chain to enhance the mechanical properties of rubber fluids.

Benefits of technology

It significantly improves the thermal conductivity, thermal resistance and mechanical properties of the copper -covering plate, reduce the water absorption and thermal expansion rate, and improve the adaptability and the adaptability of industrialized production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003900025490000021
    Figure BDA0003900025490000021
  • Figure BDA0003900025490000131
    Figure BDA0003900025490000131
  • Figure BDA0003900025490000141
    Figure BDA0003900025490000141
Patent Text Reader

Abstract

The invention discloses a glue for copper clad laminate and a preparation method of the copper clad laminate, which comprises the following components by weight: 100-120 parts of modified epoxy resin, 10-20 parts of curing agent, 20-30 parts of modified filler, 10-20 parts of polyphenylene sulfide powder, 20-30 parts of silicone resin, 1-3 parts of curing accelerator, and 40-80 parts of acetone. The copper clad laminate prepared by the present invention has higher thermal conductivity and heat-resistant temperature, and also has high peel strength and mechanical strength. At the same time, the copper clad laminate has excellent thermal reliability, low water absorption, and lower dielectric constant and dielectric loss, is easy to batch and large-scale production, and has a good industrial production basis and broad application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of copper clad laminates, and in particular relates to an adhesive for copper clad laminates and a preparation method of the copper clad laminates. Background Art

[0002] Today's society is booming towards the direction of electronics. Electronic products have flooded our world. With the development of science and technology and the diversification of application places, various high-tech devices such as mobile phones, cameras, printers, etc. are developing in the direction of being thinner and shorter. The key electronic component, the printed circuit board (PCB), is also constantly developing towards being thinner and multi-level, which puts forward higher performance requirements for the copper clad laminate as the PCB substrate.

[0003] Due to the implementation of the EU RoHS directive, the global electronics industry has already entered the era of lead-free soldering. In lead-free soldering, the melting point of the solder used is 30-40℃ higher than that of lead solder, and the soldering time above the melting point is also about 50 seconds longer. Therefore, the heat received by the board during the welding process increases greatly, which requires the copper clad laminate to have better heat resistance. The glass transition temperature of the traditional FR-4 copper clad laminate is only around 130℃, and the thermal decomposition temperature is generally only 300-310℃. The heat resistance is low. Although it can be used in general electronic products, it cannot be used in the field of high-density interconnection and integrated circuits. With the rapid development of electronic products and the rapid changes in updates, printed circuits are required to develop towards thinness and multi-layering, and the substrate material must have higher glass transition temperature, heat resistance and low expansion rate and other properties. At the same time, other properties must not be reduced to improve the reliability of interconnection and installation.

[0004] Chinese patent application No. 201710368541.3 discloses a glue for the production of lead-free high-heat-resistant copper-clad laminates. The main raw materials include: 30-60 parts of low-bromine epoxy resin, 10-30 parts of high-bromine epoxy resin, 5-10 parts of tetrafunctional epoxy resin, 20-40 parts of 4-(N-maleimide)phenol glycidyl ether, 2.5-4 parts of dicyandiamide, 0.05-0.2 parts of curing accelerator, 20-50 parts of inorganic filler, and 0.5-2 parts of silane coupling agent KH560, wherein 4-(N-maleimide)phenol glycidyl ether is synthesized from maleic anhydride, p-bromoaniline and glycidol as raw materials. The FR-4 copper clad laminate prepared by this invention has excellent comprehensive performance and meets the requirements for use in high-end PCBs. However, a large amount of inorganic fillers are used in this invention, which may cause the viscosity of the adhesive to increase, processing difficulties, poor mechanical strength and toughness of the matrix, and reduced bonding performance, thereby creating more gaps inside the system and reducing the disadvantages of electrical breakdown and insulation performance. Summary of the invention

[0005] In view of the deficiencies in the prior art, the object of the present invention is to provide an adhesive for copper clad laminates and a method for preparing copper clad laminates. The prepared copper clad laminates have high thermal conductivity and heat resistance temperature, high peel strength and mechanical strength. At the same time, the copper clad laminates have excellent thermal reliability, low water absorption, and low dielectric constant and dielectric loss. They are easy to mass-produce and have a good industrial production foundation and broad application prospects.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] A glue for copper clad laminate, comprising the following components in parts by weight:

[0008]

[0009]

[0010] Preferably, the preparation method of the modified epoxy resin comprises the following steps:

[0011] (1) adding epoxy resin, glutaraldehyde, and aminoethylaminopropyl polydimethylsiloxane into a reaction kettle, and then adding dibutyltin dilaurate, stirring and reacting, and obtaining a silicone-modified epoxy resin after the reaction is completed;

[0012] (2) The organosilicon-modified epoxy resin obtained in step (1) and heptadecafluorodecyltriethoxysilane are uniformly mixed, and then epichlorohydrin and 1,6-dihydroxynaphthalene are added to carry out a constant temperature reaction. After the reaction is completed, the modified epoxy resin is obtained.

[0013] Preferably, the epoxy resin in step (1) is one or more of bisphenol F epoxy resin and bisphenol A epoxy resin; the mass ratio of the epoxy resin, glutaraldehyde, aminoethylaminopropyl polydimethylsiloxane and dibutyltin dilaurate is 100:20-40:10-30:0.5-1; the stirring reaction temperature is 80-100°C and the reaction time is 3-6h.

[0014] Preferably, in step (2), the mass ratio of the organosilicon-modified epoxy resin, heptadecafluorodecyltriethoxysilane, epichlorohydrin and 1,6-dihydroxynaphthalene is 100:5-10:20-30:15-20; the temperature of the isothermal reaction is 100-120°C, and the reaction time is 2-5h.

[0015] Preferably, the curing agent is one or more of phthalic anhydride, trimellitic anhydride, tung oil anhydride, and methylhexahydrophthalic anhydride; the curing accelerator is one or more of imidazole, 1-benzylbenzene-2-ethylimidazole, 2-methylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 1-aminoethyl-2-methylimidazole, and 1-cyanoethylimidazole.

[0016] Preferably, the method for preparing the modified filler comprises the following steps:

[0017] (a) adding carbon nanotubes and silicon carbide powders into a potassium permanganate solution, immersing and then ball milling, followed by filtering and drying to obtain a pretreated mixed powder;

[0018] (b) adding the pretreated mixed powder in step (a) into deionized water, and then adding ammonia borane, melamine and sulfur powder, stirring to react, and after the reaction is completed, filtering, washing with water, drying, and calcining under inert gas conditions to obtain a modified mixed powder;

[0019] (c) adding the modified mixed powder obtained in step (b) and γ-glycidyloxypropyltrimethoxysilane into a ball mill and performing ball milling to obtain the modified filler.

[0020] Preferably, in step (a), the mass ratio of the carbon nanotubes to the silicon carbide powder is 1:1-2; the mass concentration of the potassium permanganate solution is 5-10%; the rotation speed of the ball mill is 1500-2500 r / min, and the ball milling time is 1-3 h.

[0021] Preferably, in step (b), the mass ratio of the pretreated mixed powder, ammonia borane, melamine and sulfur powder is 100:70-90:100-130:10-20; the temperature of the stirring reaction is 80-100°C, and the stirring time is 5-7h; the inert gas is nitrogen, the calcination temperature is 900-1100°C, and the calcination time is 2-4h; in step (c), the mass ratio of the modified mixed powder and γ-glycidyloxypropyltrimethoxysilane is 100:1-3; the rotation speed of the ball mill is 2000-2500r / min, and the time is 0.5-1h.

[0022] The present invention also protects a method for preparing the adhesive for copper clad laminate, comprising the following steps:

[0023] The raw materials are weighed according to the formula, and the modified epoxy resin, curing agent, silicone resin and curing accelerator are mixed evenly, and then acetone is added, and stirred at 50-70° C. for 1-2 hours to obtain a mixed solution; then the modified filler and polyphenylene sulfide powder are added to the mixed solution, and stirred at room temperature for 0.5-1 hour to obtain the adhesive for the copper clad laminate.

[0024] The present invention also protects a method for preparing a copper clad laminate, comprising the following steps:

[0025] Prepare a prepreg from the copper clad laminate using glue;

[0026] The semi-cured sheet and the copper foil are stacked and laminated. The lamination conditions are: temperature of 160-220° C., pressure of 2-4 MPa, and curing time of 60-90 min to obtain a copper clad laminate.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] (1) The adhesive for copper clad laminate prepared by the present invention is prepared by modifying epoxy resin. First, epoxy resin and aminoethylaminopropyl polydimethylsiloxane are cross-linked under the action of glutaraldehyde, so that organic silicon is connected to the epoxy resin, which can improve the adhesion and mechanical properties of the adhesive to copper foil, and can also improve the thermal stability, water resistance and aging resistance of the adhesive; then 1,6-dihydroxynaphthalene and heptadecafluorodecyltriethoxysilane are added to introduce a naphthalene ring polyaromatic ring structure into the resin system. The structure of the naphthalene ring is a mesh chain arrangement, and its free volume is small, which can significantly reduce the water absorption rate and thermal expansion rate. At the same time, heptadecafluorodecyltriethoxysilane can also improve the hydrophobicity of the epoxy resin and further improve the water absorption rate of the epoxy resin; in addition, the naphthalene ring structure has rigidity, which can increase the rigidity of the chain segment, so that the epoxy resin has a higher glass transition temperature, thereby significantly improving the heat resistance of the resin.

[0029] (2) The adhesive for copper clad laminate prepared by the present invention improves the compatibility of filler particles with epoxy resin and improves the mechanical properties and heat resistance of the resin; first, carbon nanotubes and silicon carbide powder are immersed in potassium permanganate solution to activate and oxidize their surfaces, which is beneficial to the subsequent reaction; then, ammonia borane, melamine and sulfur powder are added to react in situ on the surface of the pretreated mixed powder to synthesize boron nitride; the added sulfur powder can be used as a pore-forming agent to make the prepared boron nitride have a porous structure and generate a larger specific surface area, thereby improving the thermal stability and chemical stability of the epoxy resin; finally, γ-glycidyloxypropyltrimethoxysilane is ball-milled with the modified mixed powder to improve the dispersibility and compatibility of the mixed powder in the epoxy resin, so that the mechanical properties of the epoxy resin will not decrease, thereby improving the comprehensive performance of the adhesive.

[0030] (3) The adhesive for copper clad laminate prepared by the present invention improves the heat resistance of the adhesive and reduces the water absorption rate by modifying the epoxy resin itself and introducing organic silicon groups and heptadecafluorodecyltriethoxysilane; among the modified fillers added, carbon nanotubes and silicon carbide powders themselves have good thermal conductivity, and the porous boron nitride synthesized in situ on their surfaces also forms a thermal conductive network chain between the thermal conductive particles, further improving the thermal conductivity of the adhesive; the polyphenylene sulfide powder added subsequently forms a semi-interpenetrating polymer network with other components in the epoxy resin after melting, which can increase the crosslinking density and mechanical properties of the epoxy resin after curing. When the epoxy resin is heated, the internal steric hindrance increases, so that the activity of its chain segments is restricted, thereby improving the heat resistance of the epoxy resin; the adhesive prepared by the present invention significantly improves the thermal conductivity, heat resistance and mechanical properties of the adhesive for copper clad laminate through the synergistic effect between the raw materials, and has good application prospects. DETAILED DESCRIPTION

[0031] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] The bisphenol F epoxy resin was purchased from Jining Tangyi Chemical Co., Ltd., with the brand name Nan Ya NPEF-170; the bisphenol A epoxy resin was purchased from Henan Huipu Anticorrosion Materials Co., Ltd., with the brand name E-44; the silicone resin was purchased from Henan Huipu Anticorrosion Materials Co., Ltd., with the brand name SH-1053; the polyphenylene sulfide powder was purchased from Dongguan Zhengqi Plastic Raw Materials Co., Ltd., with the brand name American Chevron Philips PR-06 and the mesh number of 325 mesh; the carbon nanotubes were purchased from Jiaxing Naco New Materials Co., Ltd., with a tube diameter of 50-80nm and a tube length of 15-30μm; the particle size of the silicon carbide powder was 600-800 mesh;

[0033] Example 1

[0034] A method for preparing the adhesive for copper clad laminates comprises the following steps:

[0035] The raw materials were weighed according to the formula, 1.1 kg of modified epoxy resin, 130 g of phthalic anhydride, 230 g of silicone resin, and 20 g of 1-benzylbenzene-2-ethylimidazole were mixed evenly, and then 600 g of acetone was added, and stirred at 60° C. for 1.5 h to obtain a mixed solution; then 230 g of modified filler and 130 g of polyphenylene sulfide powder were added to the mixed solution, and stirred at room temperature for 1 h to obtain the adhesive for the copper clad laminate.

[0036] Wherein, the preparation method of the modified epoxy resin comprises the following steps:

[0037] (1) 100 g of bisphenol F epoxy resin, 30 g of glutaraldehyde, and 20 g of aminoethylaminopropyl polydimethylsiloxane were added to a reaction kettle, followed by adding 0.8 g of dibutyltin dilaurate, and stirred at 90° C. for 5 h to obtain a silicone-modified epoxy resin;

[0038] (2) The organosilicon-modified epoxy resin (100 g) obtained in step (1) and 8 g of heptadecafluorodecyltriethoxysilane were mixed evenly, and then 24 g of epichlorohydrin and 18 g of 1,6-dihydroxynaphthalene were added, and the mixture was reacted at a constant temperature of 110° C. for 4 h. After the reaction was completed, the modified epoxy resin was obtained.

[0039] The preparation method of the modified filler comprises the following steps:

[0040] (a) adding 50 g of carbon nanotubes and 80 g of silicon carbide powder into 300 mL of 8% potassium permanganate solution, immersing for 5 h, and then ball milling at a speed of 2000 r / min for 2 h, followed by filtering and drying to obtain a pretreated mixed powder;

[0041] (b) adding the pretreated mixed powder (100 g) in step (a) to 800 mL of deionized water, followed by adding 80 g of ammonia borane, 120 g of melamine, and 14 g of sulfur powder, stirring and reacting at 90° C. for 6 h, filtering after the reaction, washing with water, drying, and calcining under nitrogen atmosphere at a temperature of 1000° C. for 3 h to obtain a modified mixed powder;

[0042] (c) adding the modified mixed powder (100 g) obtained in step (b) and 2 g of γ-glycidyloxypropyltrimethoxysilane into a ball mill and performing ball milling at a speed of 2400 r / min for 1 h to obtain the modified filler.

[0043] Example 2

[0044] A method for preparing the adhesive for copper clad laminates comprises the following steps:

[0045] The raw materials were weighed according to the formula, 1.1 kg of modified epoxy resin, 170 g of methylhexahydrophthalic anhydride, 270 g of silicone resin, and 25 g of 1-benzylbenzene-2-ethylimidazole were mixed evenly, and then 700 g of acetone was added, and stirred at 60° C. for 1.5 h to obtain a mixed solution; then 270 g of modified filler and 170 g of polyphenylene sulfide powder were added to the mixed solution, and stirred at room temperature for 0.5 h to obtain the adhesive for the copper clad laminate.

[0046] Wherein, the preparation method of the modified epoxy resin comprises the following steps:

[0047] (1) 100 g of bisphenol A epoxy resin, 30 g of glutaraldehyde, and 25 g of aminoethylaminopropyl polydimethylsiloxane were added to a reaction kettle, followed by adding 0.7 g of dibutyltin dilaurate, and stirred at 90° C. for 4 h to obtain a silicone-modified epoxy resin;

[0048] (2) The organosilicon-modified epoxy resin (100 g) obtained in step (1) and 7 g of heptadecafluorodecyltriethoxysilane were mixed evenly, and then 27 g of epichlorohydrin and 17 g of 1,6-dihydroxynaphthalene were added, and the mixture was reacted at a constant temperature of 110° C. for 3 h. After the reaction was completed, the modified epoxy resin was obtained.

[0049] The preparation method of the modified filler comprises the following steps:

[0050] (a) adding 50 g of carbon nanotubes and 70 g of silicon carbide powder into 300 mL of a 7% potassium permanganate solution, immersing for 4 h, and then ball milling at a speed of 2200 r / min for 2 h, followed by filtering and drying to obtain a pretreated mixed powder;

[0051] (b) adding the pretreated mixed powder (100 g) in step (a) to 800 mL of deionized water, followed by adding 80 g of ammonia borane, 110 g of melamine, and 17 g of sulfur powder, stirring and reacting at 90 ° C for 6 h, filtering after the reaction, washing with water, drying, and calcining under nitrogen atmosphere at a temperature of 1000 ° C for 3 h to obtain a modified mixed powder;

[0052] (c) adding the modified mixed powder (100 g) obtained in step (b) and 2 g of γ-glycidyloxypropyltrimethoxysilane into a ball mill and subjecting the mixture to ball milling at a speed of 2200 r / min for 1 h to obtain the modified filler.

[0053] Example 3

[0054] A method for preparing the adhesive for copper clad laminates comprises the following steps:

[0055] The raw materials were weighed according to the formula, 1 kg of modified epoxy resin, 100 g of trimellitic anhydride, 200 g of silicone resin, and 10 g of 2-phenylimidazole were mixed evenly, and then 400 g of acetone was added, and stirred at 50° C. for 2 h to obtain a mixed solution; then 200 g of modified filler and 100 g of polyphenylene sulfide powder were added to the mixed solution, and stirred at room temperature for 0.5 h to obtain the adhesive for the copper clad laminate.

[0056] Wherein, the preparation method of the modified epoxy resin comprises the following steps:

[0057] (1) 100 g of bisphenol F epoxy resin, 20 g of glutaraldehyde, and 10 g of aminoethylaminopropyl polydimethylsiloxane were added to a reaction kettle, followed by adding 0.5 g of dibutyltin dilaurate, and stirred at 80° C. for 6 h to obtain a silicone-modified epoxy resin;

[0058] (2) The organosilicon-modified epoxy resin (100 g) obtained in step (1) and 5 g of heptadecafluorodecyltriethoxysilane were mixed evenly, and then 20 g of epichlorohydrin and 15 g of 1,6-dihydroxynaphthalene were added, and the mixture was reacted at a constant temperature of 100° C. for 5 h. After the reaction was completed, the modified epoxy resin was obtained.

[0059] The preparation method of the modified filler comprises the following steps:

[0060] (a) adding 50 g of carbon nanotubes and 50 g of silicon carbide powder into 300 mL of a 5% potassium permanganate solution, immersing for 3 h, and then ball milling at a speed of 1500 r / min for 3 h, followed by filtering and drying to obtain a pretreated mixed powder;

[0061] (b) adding the pretreated mixed powder (100 g) in step (a) to 800 mL of deionized water, followed by adding 70 g of ammonia borane, 100 g of melamine, and 10 g of sulfur powder, stirring and reacting at 80 ° C for 5 h, filtering after the reaction, washing with water, drying, and calcining under nitrogen atmosphere at a temperature of 900 ° C for 4 h to obtain a modified mixed powder;

[0062] (c) adding the modified mixed powder (100 g) obtained in step (b) and 1 g of γ-glycidyloxypropyltrimethoxysilane into a ball mill and performing ball milling at a speed of 2000 r / min for 1 h to obtain the modified filler.

[0063] Example 4

[0064] A method for preparing the adhesive for copper clad laminates comprises the following steps:

[0065] The raw materials were weighed according to the formula, 1.2 kg of modified epoxy resin, 200 g of methylhexahydrophthalic anhydride, 300 g of silicone resin, and 30 g of 2-ethyl-4-methylimidazole were mixed evenly, and then 800 g of acetone was added, and stirred at 70° C. for 1 hour to obtain a mixed solution; then 300 g of modified filler and 200 g of polyphenylene sulfide powder were added to the mixed solution, and stirred at room temperature for 1 hour to obtain the adhesive for copper clad laminates.

[0066] Wherein, the preparation method of the modified epoxy resin comprises the following steps:

[0067] (1) 100 g of bisphenol A epoxy resin, 40 g of glutaraldehyde, and 30 g of aminoethylaminopropyl polydimethylsiloxane were added to a reaction kettle, followed by adding 1 g of dibutyltin dilaurate, and stirred at 100° C. for 3 h to obtain a silicone-modified epoxy resin after the reaction was completed;

[0068] (2) The organosilicon-modified epoxy resin (100 g) obtained in step (1) and 10 g of heptadecafluorodecyltriethoxysilane were mixed evenly, and then 30 g of epichlorohydrin and 20 g of 1,6-dihydroxynaphthalene were added, and the mixture was reacted at a constant temperature of 120° C. for 2 h. After the reaction was completed, the modified epoxy resin was obtained.

[0069] The preparation method of the modified filler comprises the following steps:

[0070] (a) adding 50 g of carbon nanotubes and 100 g of silicon carbide powder into 300 mL of a 10% potassium permanganate solution, immersing for 6 h, and then ball milling at a speed of 2500 r / min for 1 h, followed by filtering and drying to obtain a pretreated mixed powder;

[0071] (b) adding the pretreated mixed powder (100 g) in step (a) into 800 mL of deionized water, followed by adding 90 g of ammonia borane, 130 g of melamine and 20 g of sulfur powder, stirring and reacting at 100 ° C for 5 h, filtering after the reaction, washing with water, drying, and calcining under nitrogen atmosphere at a temperature of 1100 ° C for 2 h to obtain a modified mixed powder;

[0072] (c) adding the modified mixed powder (100 g) obtained in step (b) and 3 g of γ-glycidyloxypropyltrimethoxysilane into a ball mill and performing ball milling at a speed of 2500 r / min for 0.5 h to obtain the modified filler.

[0073] Comparative Example 1

[0074] A method for preparing the adhesive for copper clad laminates comprises the following steps:

[0075] The raw materials were weighed according to the formula, 1.1 kg of epoxy resin, 130 g of phthalic anhydride, 230 g of silicone resin, and 20 g of 1-benzylbenzene-2-ethylimidazole were mixed evenly, and then 600 g of acetone was added, and stirred at 60° C. for 1.5 hours to obtain a mixed solution; then 230 g of modified filler and 130 g of polyphenylene sulfide powder were added to the mixed solution, and stirred at room temperature for 1 hour to obtain the adhesive for the copper clad laminate.

[0076] The preparation method of the modified filler comprises the following steps:

[0077] (a) adding 50 g of carbon nanotubes and 80 g of silicon carbide powder into 300 mL of 8% potassium permanganate solution, immersing for 5 h, and then ball milling at a speed of 2000 r / min for 2 h, followed by filtering and drying to obtain a pretreated mixed powder;

[0078] (b) adding the pretreated mixed powder (100 g) in step (a) to 800 mL of deionized water, followed by adding 80 g of ammonia borane, 120 g of melamine, and 14 g of sulfur powder, stirring and reacting at 90° C. for 6 h, filtering after the reaction, washing with water, drying, and calcining under nitrogen atmosphere at a temperature of 1000° C. for 3 h to obtain a modified mixed powder;

[0079] (c) adding the modified mixed powder (100 g) obtained in step (b) and 2 g of γ-glycidyloxypropyltrimethoxysilane into a ball mill and performing ball milling at a speed of 2400 r / min for 1 h to obtain the modified filler.

[0080] Comparative Example 2

[0081] A method for preparing the adhesive for copper clad laminates comprises the following steps:

[0082] The raw materials were weighed according to the formula, 1.1 kg of modified epoxy resin, 130 g of phthalic anhydride, 230 g of silicone resin, and 20 g of 1-benzylbenzene-2-ethylimidazole were mixed evenly, and then 600 g of acetone was added, and stirred at 60° C. for 1.5 hours to obtain a mixed solution; then 230 g of filler and 130 g of polyphenylene sulfide powder were added to the mixed solution, and stirred at room temperature for 1 hour to obtain the adhesive for the copper clad laminate.

[0083] Wherein, the preparation method of the modified epoxy resin comprises the following steps:

[0084] (1) 100 g of bisphenol F epoxy resin, 30 g of glutaraldehyde, and 20 g of aminoethylaminopropyl polydimethylsiloxane were added to a reaction kettle, followed by adding 0.8 g of dibutyltin dilaurate, and stirred at 90° C. for 5 h to obtain a silicone-modified epoxy resin;

[0085] (2) The organosilicon-modified epoxy resin (100 g) obtained in step (1) and 8 g of heptadecafluorodecyltriethoxysilane were mixed evenly, and then 24 g of epichlorohydrin and 18 g of 1,6-dihydroxynaphthalene were added, and the mixture was reacted at a constant temperature of 110° C. for 4 h. After the reaction was completed, the modified epoxy resin was obtained.

[0086] The filler is prepared by ball milling 50g of carbon nanotubes and 80g of silicon carbide powder, the rotation speed of the ball mill is 2000r / min, and the ball milling time is 2h.

[0087] The adhesive for copper clad laminates prepared in Examples 1-4 and Comparative Examples 1-2 was impregnated with E-glass fiber cloth to prepare prepregs, and the prepregs were stacked with copper foil and laminated at a temperature of 220° C., a pressure of 3 MPa, and a curing time of 80 min to prepare copper clad laminates. The copper clad laminates prepared by the glues of Examples 1-4 and Comparative Examples 1-2 were subjected to performance tests, wherein the thermal conductivity test method was carried out according to the ASTM-5470 method; the water absorption was tested according to GB / T1462-2005, and the copper clad laminates were immersed in a constant temperature water bath at 25°C for 24 hours, and the mass changes before and after immersion were measured to determine the water absorption of the copper clad laminates; the peel strength was tested according to GB / T 4722-2017; the flexural strength was tested according to the standard GB / T 2567-2021, and the flexural strength specimen size was 4.0 mm in thickness, 100 mm in length, and 15 mm in width, the test speed was 10 mm / min, the number of tests was 5, the test temperature was 23°C, the relative humidity was 50%, and the specimen conditioning time was 30 hours; PCT was cooked in a 121°C 105KPa pressure cooker for 1 hour, immersed in a 288°C tin furnace, and the bursting board delamination time was recorded; the test results are as shown in Table 1 below:

[0088] Table 1

[0089]

[0090]

[0091] It can be seen from Table 1 above that the adhesive for copper clad laminate prepared by the present invention has good heat resistance and low water absorption, and the added modified filler has no effect on its mechanical properties, so that the prepared copper clad laminate has good peel strength, thermal conductivity and bending strength, and has good application prospects.

[0092] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A glue for copper clad laminate, characterized in that: By weight, it includes the following components: The preparation method of the modified epoxy resin comprises the following steps: (1) adding epoxy resin, glutaraldehyde, and aminoethylaminopropyl polydimethylsiloxane into a reaction kettle, and then adding dibutyltin dilaurate, stirring and reacting, and obtaining a silicone-modified epoxy resin after the reaction is completed; (2) mixing the organosilicon-modified epoxy resin obtained in step (1) and heptadecafluorodecyltriethoxysilane uniformly, then adding epichlorohydrin and 1,6-dihydroxynaphthalene, and reacting at a constant temperature to obtain the modified epoxy resin after the reaction is completed; The epoxy resin in step (1) is one or more of bisphenol F epoxy resin and bisphenol A epoxy resin; the mass ratio of the epoxy resin, glutaraldehyde, aminoethylaminopropyl polydimethylsiloxane and dibutyltin dilaurate is 100:20-40:10-30:0.5-1; the stirring reaction temperature is 80-100°C and the reaction time is 3-6h; In step (2), the mass ratio of the organosilicon-modified epoxy resin, heptadecafluorodecyltriethoxysilane, epichlorohydrin, and 1,6-dihydroxynaphthalene is 100:5-10:20-30:15-20; the temperature of the isothermal reaction is 100-120° C., and the reaction time is 2-5 hours; The preparation method of the modified filler comprises the following steps: (a) adding carbon nanotubes and silicon carbide powders into a potassium permanganate solution, immersing and then ball milling, followed by filtering and drying to obtain a pretreated mixed powder; (b) adding the pretreated mixed powder in step (a) into deionized water, and then adding ammonia borane, melamine and sulfur powder, stirring to react, and after the reaction is completed, filtering, washing with water, drying, and calcining under inert gas conditions to obtain a modified mixed powder; (c) adding the modified mixed powder obtained in step (b) and γ-glycidyloxypropyltrimethoxysilane into a ball mill, and performing ball milling to obtain the modified filler; The mass ratio of the carbon nanotubes to the silicon carbide powder in step (a) is 1:1-2; the mass concentration of the potassium permanganate solution is 5-10%; the rotation speed of the ball mill is 1500-2500 r / min, and the ball milling time is 1-3 h; In step (b), the mass ratio of the pretreated mixed powder, ammonia borane, melamine and sulfur powder is 100:70-90:100-130:10-20; the temperature of the stirring reaction is 80-100°C and the stirring time is 5-7h; the inert gas is nitrogen, the calcination temperature is 900-1100°C and the calcination time is 2-4h; in step (c), the mass ratio of the modified mixed powder and γ-glycidyloxypropyltrimethoxysilane is 100:1-3; the rotation speed of the ball mill is 2000-2500r / min and the time is 0.5-1h.

2. The adhesive for copper clad laminate according to claim 1, characterized in that: The curing agent is one or more of phthalic anhydride, trimellitic anhydride, tung oil anhydride, and methyl hexahydrophthalic anhydride; the curing accelerator is one or more of imidazole, 1-benzylbenzene-2-ethylimidazole, 2-methylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 1-aminoethyl-2-methylimidazole, and 1-cyanoethylimidazole.

3. A method for preparing the adhesive for copper clad laminate according to any one of claims 1 to 2, characterized in that: The following steps are involved: The raw materials are weighed according to the formula, and the modified epoxy resin, curing agent, silicone resin and curing accelerator are mixed evenly, and then acetone is added, and stirred at 50-70° C. for 1-2 hours to obtain a mixed solution; then the modified filler and polyphenylene sulfide powder are added to the mixed solution, and stirred at room temperature for 0.5-1 hour to obtain the adhesive for the copper clad laminate.

4. A method for preparing a copper clad laminate, characterized in that: The following steps are involved: Prepare a prepreg using the adhesive for the copper clad laminate according to any one of claims 1-2; The semi-cured sheet and the copper foil are stacked and laminated. The lamination conditions are: temperature of 160-220° C., pressure of 2-4 MPa, and curing time of 60-90 min to obtain a copper clad laminate.

Citation Information

Patent Citations

  • Leadless high-heat resistance glue solution for producing copper-clad plates

    CN107245221A

  • Modified epoxide resin-based prepreg used for copper-clad plate and preparation method of modified epoxide resin-based prepreg

    CN107759977A

  • High-frequency heat-conducting substrate and preparation method thereof

    CN111844951A